Building a Sustainable Campus: The Role of Green Leadership in the Sustainability Performance of Higher Education in the City of Bandung through Green Organizational Behavior - Yani Restiani Widjaja; Purwadhi Purwadhi (Greenation Research & Yayasan Global Resarch National, 2026)
Sustainable campus development is one of the strategic efforts of universities in supporting the sustainable development agenda and answering the challenges of environmental problems. This study aims to analyze the role of green leadership in the sustainability performance of universities in the city of Bandung through green organizational behavior. This study uses a quantitative approach with a survey method of the academic community consisting of lecturers, education staff, and leaders of units/faculties/study programs at universities in the city of Bandung, with a total of 160 samples. The research data was collected through the distribution of questionnaires and analyzed using the SEM PLS statistical analysis technique to test the relationship between the variables studied. The results of the study show that green leadership has a positive influence on green organizational behavior. In addition, green organizational behavior also plays a role in improving the sustainability performance of universities. The findings of this study show that environmentally oriented organizational behavior can be an important mechanism that bridges the influence of environmentally sound leadership on improving institutional sustainability performance. Thus, the implementation of green leadership supported by environmentally friendly organizational behavior can encourage the realization of a more sustainable campus.